1999
DOI: 10.1097/00007890-199905150-00003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Complications of the Piggy-Back Technique in 1,112 Liver Transplants

Abstract: The vena cava preservation technique can be used routinely in orthotopic liver transplantation because it is safe and efficient and involves few surgical complications especially if for venous reconstruction we use the patch obtained by joining the three suprahepatic veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
1
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(84 citation statements)
references
References 11 publications
1
77
1
5
Order By: Relevance
“…Clinical presentation ranges from lower limb edema, hepatomegaly, ascites, pleural effusions, BuddChiari syndrome, liver and renal failure to hypotension leading to allograft loss and multiorgan failure [4,89,135] . The main risk factor leading to caval anastomosis complications (CACs) is represented by technical errors in the connection of caval anastomoses, which lead to kinking or thrombosis in the early postoperative course.…”
Section: Caval Vein Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical presentation ranges from lower limb edema, hepatomegaly, ascites, pleural effusions, BuddChiari syndrome, liver and renal failure to hypotension leading to allograft loss and multiorgan failure [4,89,135] . The main risk factor leading to caval anastomosis complications (CACs) is represented by technical errors in the connection of caval anastomoses, which lead to kinking or thrombosis in the early postoperative course.…”
Section: Caval Vein Complicationsmentioning
confidence: 99%
“…The method described by Starzl et al [138] (1968) consists of a complete resection of the recipient IVC and interposition of the donor intrahepatic part of the vena cava with two endtoend anastomoses [138144] . The preservation of the recipient IVC with the PB technique has been associated with an increased risk of suprahepatic IVC thrombosis or stenosis, leading to acute or chronic BuddChiari syndrome in 0% to 1.6%, venous congestion of the liver allograft in 1%, and with an increased incidence of posttransplant ascites [89,135] . To avoid such complications, techniques for optimizing outflow with the piggyback technique have been described; the main of these in undoubtfully the width of the caval anastomosis, while other authors have reported methods using either the twovein or the threevein technique for anastomosis with a low rate of CACs [89,94,135,145149] .…”
Section: Caval Vein Complicationsmentioning
confidence: 99%
“…The manifestations of limited outflow depend on the degree and range from mild graft dysfunction and/or ascites to rapidly progressive liver failure and/or refractory ascites. 96,97 The drainage pattern of the liver and the anatomic relationships of the hepatic veins dictate which veins are taken with the resected segment for LDLT. There is a great deal of overlap between the venous drainage territories, and the veins can be managed in more than one way without deleterious consequences for the graft or the remnant lobe.…”
Section: Recipient Outflow and The Issue Of The Midhepatic Veinmentioning
confidence: 99%
“…1 Although venous complications occur, they tend to develop insidiously and seldom precipitate acute graft failure. 2 Intact organs and segmental grafts most commonly used (left lateral segments and full left lobes) retain many of the usual avenues for outflow. 3 Left grafts no longer sharing the midhepatic vein (MHV) with the right lobe might even be considered outflow privileged.…”
mentioning
confidence: 99%